What's so great about fourth graden - Kahaner, Ellen; Henry, Paul 1956-. (Mahwah, NJ Troll Associates, 1990)
A lie from his brainy best friend threatens to bar Mark from playing baseball for his fourth grade team.
Keywords: Friendship -- Fiction; Schools -- Fiction; Baseball -- Fiction